Geomorphologische Studien an Schuttfächern in Ostkreta: Ein Beitrag zur Klimageschichte des Jungquartärs in Mittelmeerländern - Hempel, Ludwig (ERDKUNDE, 1984)
The author has investigated sedimentation cycles within alluvial fans in the high mountains of Crete. They provide an insight into the palaeoclimatic situation during late-quaternary times. The period from the high Wurm glaciation to the present time is illuminated by sequences of debris masses moved by solifluction, fluvial transport and torrential washes. Consolidated material (breccia) gives evidence of warm interstadials. The Holocene can be divided into two periods characterized by torrential transport of weathered material. They are separated by a short humid phase. During this time the surface of older debris layers was converted into breccia. The origin of the older debris dates back to times prior to human influences on the ecosystems. The most recent debris complex can be parallelled with the historical fills of the basin landscapes. With regard to the total volume of the alluvial fan, it is relatively small. Roughly calculated it comprises about 20% of the total debris masses of late-quaternary (Wurm glaciation till present). By historiograms (orientation, roudness) the sediments of the high zone are affilated to the dated sediments of the coastal plains, along the course of a valley extending from the sea shore to the high mountains area. This valley offers the only opportunity to indicate the lower limit of solifluction processes fairly reliably, probably because of the high amount of water. It must be left undecided whether the torrential sediments at an altitude of about 600 m a.s.l. are the result of Pleistocene melt water run off or of heavy rain fall run off during the warmer period.